Emerging technologies and changing dimensions of libraries and information services - International Symposium on Emerging Trends and Technologies in Libraries and Information Services 2010 : Jaypee University of Information Technology); Kataria, Sanjay; Anbu K., John Paul; Shri Ram; Jaypee University of Information Technology (New Delhi : K.B.D. Publication, 2010)
Contributed articles presented at the second ETTLIS Symposium also held in 2008 as International Symposium on Emerging Trends and Technologies in Libraries and Information Services moderated by Jaypee University of Information Technology on June 3-5, 2010 at Waknaghat, Himachal Pradesh.
Includes bibliographical references and index.
Keywords: Library science -- Congresses; Information science -- Congresses